INVESTIGATION OF THE PHENOMENON AND IMPACT OF FISCAL POLICY ON ECONOMIC GROWTH IN INDONESIA - Hotsawadi Hotsawadi; Yesi Aprianti; Imelda Veronica Gea; Emmilya Umma Aziza Gaffar; Rian Hilmawan (EKUITAS (Jurnal Ekonomi dan Keuangan), 2026)
The rate of economic growth in Indonesia's provinces remains relatively lower than the national average. This phenomenon poses a significant challenge for the government in achieving the 8% economic development target outlined in the RPJMN text from 2025 to 2029. One of the essential instruments the government to achieve national economic growth targets is fiscal policy. For this reason, this study aims to identify the phenomenon and impact of fiscal policy on economic growth using the ARDL panel analysis method. The dependent variable is the economic growth rate for districts/cities in Indonesia. In contrast, the independent variable includes fiscal policy instruments consisting of local original revenues, regional transfer funds, public service spending, the economy, and tourism. The analysis results show that the variables of fiscal policy instruments, consisting of regional original income, regional transfer funds, economy, and tourism, have a positive effect on the long-term regional economy in Indonesia. Meanwhile, public service expenditure is harmful to the regional economy in the long term.